Macroeconomic Implications of Natural Disasters in the Caribbean - Rasmussen, Tobias (Washington, D.C. : International Monetary Fund, 2004)
Each year natural disasters affect about 200 million people and cause about USD 50 billion in damage. This paper compares the incidence of natural disasters across countries along several dimensions and finds that the relative costs tend to be far higher in developing countries than in advanced economies. The analysis shows that small island states are especially vulnerable, with the countries of the Eastern Caribbean standing out as among the most disaster-prone in the world. Natural disasters are found to have had a discernible macroeconomic impact, including large effects on fiscal and external balances, pointing to an important role for precautionary measures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet